2021
DOI: 10.1002/oby.23065
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine‐Induced Aryl Hydrocarbon Receptor Signaling in Mice Causes Body Mass Gain, Liver Steatosis, and Hyperglycemia

Abstract: Objective: The aryl hydrocarbon receptor (AHR) plays a key role in obesity. In vitro studies revealed that the tryptophan metabolite kynurenine (Kyn) activates AHR signaling in cultured hepatocytes. The objective of this study was to determine whether Kyn activated the AHR in mice to induce obesity. Methods: Mice were fed a low-fat diet and the same diet supplemented with Kyn. Body mass, liver status, and the expression of identified relevant genes were determined. Results: Kyn caused mice to gain significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 44 publications
(86 reference statements)
2
25
0
Order By: Relevance
“…Consequently, Moyer et al (2016) proposed that a sustained increase in Kyn-induced AHR activity derived from the excess consumption of Western diet helped to promote the obese phenotype. This hypothesis was further tested rigorously in vivo by the Tomlinson group, who subsequently showed that the addition of Kyn to a low-fat diet induced AHR activity in mice to cause weight gain, fatty liver, and hyperglycemia (Rojas et al 2020, in press) [89]. Consistent with their previous findings, cytochrome P450 1B1 (CYP1B1) and stearoyl-coA desaturase 1 (SCD1) appeared to act as downstream effectors of Kyn-induced AHR signaling.…”
Section: Part Iii: Antagonist Theory: Ahr Inhibition As a Means For Treating Obesitymentioning
confidence: 79%
See 1 more Smart Citation
“…Consequently, Moyer et al (2016) proposed that a sustained increase in Kyn-induced AHR activity derived from the excess consumption of Western diet helped to promote the obese phenotype. This hypothesis was further tested rigorously in vivo by the Tomlinson group, who subsequently showed that the addition of Kyn to a low-fat diet induced AHR activity in mice to cause weight gain, fatty liver, and hyperglycemia (Rojas et al 2020, in press) [89]. Consistent with their previous findings, cytochrome P450 1B1 (CYP1B1) and stearoyl-coA desaturase 1 (SCD1) appeared to act as downstream effectors of Kyn-induced AHR signaling.…”
Section: Part Iii: Antagonist Theory: Ahr Inhibition As a Means For Treating Obesitymentioning
confidence: 79%
“…Having shown that activation of the AHR promoted obesity, and AHR inhibition prevented obesity, a remaining key question was whether AHR inhibition could also reverse obesity and its associated comorbidities. This question was answered recently in a study by Rojas et al (2020). Their data specifically demonstrated that obese C57BL6/J mice maintained on a Western diet, when switched to a Western diet containing the AHR antagonist αNF, lost body mass to a degree in which the mass of these mice nearly matched that of control mice maintained on a low-fat diet [90].…”
Section: Part Iii: Antagonist Theory: Ahr Inhibition As a Means For Treating Obesitymentioning
confidence: 99%
“… 37 have indicated that KYN caused body mass gain in mice with a low-fat diet, developed a fatty liver and hyperglycaemia and increased liver Cyp1b1 and Scd1 gene expression. The authors concluded that AhR activation by KYN may be necessary but insufficient for the development of obesity and that excess caloric consumption is also required for a full manifestation of obesity 37 . The above results are in agreement with our results in which we did not observe any weight gain in the animals administered KYN and fed a normal diet.…”
Section: Discussionmentioning
confidence: 99%
“…Within the cell, unique components of clozapine's chemical structure, that is a halogenated diazepine, might trigger specific cellular responses such as activation of the aryl hydrocarbon receptor (AhR). Our assumption that this ligand-activated transcription factor plays a key role in clozapine-triggered adverse effects is supported by the fact that AhR signaling causes weight gain, hyperglycemia, and hypertension (Chang et al, 2017;Rojas et al, 2021) too. Besides activation of detoxification processes, the AhR is also involved in cell differentiation, angiogenesis, and stress responses.…”
Section: Introductionmentioning
confidence: 93%
“…Beside transcriptional upregulation of drug-metabolizing enzymes, the receptor activates multiple genomic as well as non-genomic pathways involved in stem cell differentiation, cell plasticity, and immunosuppression (Abel and Haarmann-Stemmann, 2010;Matsumura, 2009). In addition, PAH exposure as well as clozapine treatment increase the risk of bone marrow toxicity (Lee et al, 2004;Luster et al, 1985) and liver steatosis (Rojas et al, 2021;Von Wilmsdorff et al, 2014) as well as the incidence of diabetes, abdominal obesity (Lee et al, 2014;Teff and Kim, 2011), and hypertension (Alberich et al, 2019;Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%